Acetaminophen use and prognosis in cancer patients treated with immune checkpoint inhibitors: evidence from a meta-analysis - Lin, Yuxuan; Liao, Yonghe; Shen, Jinhai (Frontiers in Immunology, 2025)
BackgroundEmerging studies have investigated the association between acetaminophen (APAP) use and clinical outcomes in cancer patients receiving immune checkpoint inhibitors (ICIs), but their findings remain inconsistent. This meta-analysis aims to systematically synthesize available evidence to clarify this relationship and provide evidence-based guidance for clinical practice.MethodsA systematic literature search was performed to identify studies comparing prognostic outcomes between APAP users and non-users among cancer patients treated with ICIs. Eligible studies were required to report hazard ratios (HRs) for overall survival (OS) and/or progression-free survival (PFS) with 95% confidence intervals (CIs). Meta-analyses were conducted to derive pooled effect estimates. Funnel plots and Egger’s test were used to assess publication bias, and sensitivity analyses via a leave-one-out approach were performed to evaluate the robustness of results.ResultsFive studies encompassing 7 cohorts and 2,349 patients (1,306 APAP users and 1,043 non-users) were included. Pooled analyses revealed that concomitant APAP use was significantly associated with shorter OS (HR: 1.29; 95% CI: 1.16–1.44) and PFS (HR: 1.27; 95% CI: 1.12–1.43), as well as a trend toward a lower objective response rate (RR: 0.78; 95% CI: 0.60–1.00). No significant publication bias was detected, and sensitivity analyses confirmed the robustness of these findings.ConclusionCurrent evidence indicates that APAP use is associated with poorer prognosis in cancer patients treated with ICIs. These results may inform clinical guidelines regarding concomitant APAP and ICI use. Further randomized controlled trials are warranted to validate these observations and establish causal relationships.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251118489.